2000
DOI: 10.1046/j.1462-5822.2000.00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct pathways for the invasion of Streptococcus pyogenes in non-phagocytic cells

Abstract: Adherence to and invasion of epithelial cells represent important pathogenic mechanisms of Streptococcus pyogenes. A fibronectin‐binding surface protein of S. pyogenes, SfbI protein, has been implicated in both adherence and invasion processes. Invasion of SfbI‐containing strains has been suspected to be responsible for the failure of antibiotics treatment to eradicate S. pyogenes. In this study, we tested the adherence and invasion properties of two well‐characterized clinical isolates: A40, which expresses S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 35 publications
7
93
1
1
Order By: Relevance
“…Our results agree well with recent findings that, following internalization, GAS escape from endocytic vacuoles into the cytosol, where they can multiply (Molinari et al, 2000).…”
Section: Gas Internalization and De Novo Protein Synthesis Are Necesssupporting
confidence: 93%
See 2 more Smart Citations
“…Our results agree well with recent findings that, following internalization, GAS escape from endocytic vacuoles into the cytosol, where they can multiply (Molinari et al, 2000).…”
Section: Gas Internalization and De Novo Protein Synthesis Are Necesssupporting
confidence: 93%
“…Recent studies which demonstrated that some GAS strains are capable of intracellular multiplication (Molinari et al, 2000(Molinari et al, , 2001) support the first and last hypotheses.…”
Section: Fate Of Gas Following Internalizationmentioning
confidence: 82%
See 1 more Smart Citation
“…The capacity to bind Fn renders these bacteria capable of employing integrins as receptors for efficient internalization. Extensive studies established that ␣5␤1 integrin is the primary receptor for M1-mediated (8,34) and PrtF1-mediated GAS invasion of epithelial cells (9,11). Integrin signaling required for Streptococcus internalization has only recently been investigated (10,12,35).…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria can express several invasins, but the Fn-binding proteins (FnBPs), M1 and PrtF1͞Sfb1, have been studied in most detail (9)(10)(11). Engagement of ␣5␤1 integrin with Fn bound to these proteins initiates phosphoinositide 3-kinase (10,12) and integrin-linked kinase-dependent intracellular signals that induce cytoskeletal rearrangement and ingestion of streptococci (10).…”
mentioning
confidence: 99%